Health status and risk factors associated with failure of passive transfer of immunity in newborn beef calves in Québec - Filteau, Virginie (2003)
Risk factors associated with failure of passive transfer of immunity (FPT) were evaluated among newborn beef calves in Québec. Physical examination was performed on calves born of a normal calving and blood samples were collected for determination of health status and measurement of serum concentration of immunoglobulin (Ig) G(1). Of 225 calves, from 45 herds, 19 % showed FPT (serum IgG1 concentration < 10.0 g/L). Calves born in a stanchion-stall were more likely to show FPT (OR: 10.2). Calves bottle-fed colostrum were less at risk for FPT (OR: 0.06). Calf gender, month of birth, dam parity, and dam body condition score were not associated with FPT. No association was detected between FPT and health status. Special care should be given to calves born from cows in a stanchion-stall to ensure adequate colostrum intake. Failure of passive transfer of immunity should be considered with other risk factors when investigating morbidity.